STATE LIABILITY IN EFFORTS TO PROTECT PATIENTS' RIGHTS TO CHOOSE HEALTH CARE FACILITIES IN THE FORM OF VACCINES AS A FORM OF HUMAN RIGHTS ENFORCEMENT - Fikri, Abidin (International Journal of Social Service and Research, 2024)
Health is a fundamental aspect of human life, and the right to choose health care facilities, including vaccination, is crucial to the enforcement of human rights. In the digital age, the role of Artificial Intelligence (AI) in optimizing health services, particularly in vaccination distribution and monitoring, has become significant. AI systems can enhance transparency, accuracy, and accessibility in providing health care, but they also raise questions about accountability and ethical concerns. This study examines the state's responsibility in regulating the use of AI for the protection of patients' rights, focusing on AI's role in ensuring safe, licensed vaccines for children and equitable access to healthcare facilities. The study also analyses how AI could improve the state's efforts in fulfilling its human rights obligations by making healthcare more efficient and inclusive. A normative juridical method is employed, using a statutory and analytical approach, to explore the legal frameworks governing AI in health care and the state's responsibility. The findings reveal gaps in current legal protections against the use of unlicensed vaccines, and the unequal access to AI-supported health services for vulnerable groups, such as children. While AI can help identify and distribute vaccines more effectively, the state has yet to fully implement regulations that guarantee fairness and safety in AI-driven health services. The integration of AI into healthcare poses both opportunities and challenges, and the state must strengthen its accountability mechanisms to ensure AI supports human rights, especially children's right to access safe and reliable vaccinations.